Empirical estimates of regional carbon budgets imply reduced global soil heterotrophic respiration. Issue 2 (7th July 2020) - Ciais, Philippe; Yao, Yitong; Gasser, Thomas; Baccini, Alessandro; Wang, Yilong; Lauerwald, Ronny; Peng, Shushi; Bastos, Ana; Li, Wei; Raymond, Peter A; Canadell, Josep G; Peters, Glen P; et al.
Abstract: Resolving regional carbon budgets is critical for informing land-based mitigation policy. For nine regions covering nearly the whole globe, we collected inventory estimates of carbon-stock changes complemented by satellite estimates of biomass changes where inventory data are missing. The net land–atmospheric carbon exchange (NEE) was calculated by taking the sum of the carbon-stock change and lateral carbon fluxes from crop and wood trade, and riverine-carbon export to the ocean. Summing up NEE from all regions, we obtained a global 'bottom-up' NEE for net land anthropogenic CO2 uptake of –2.2 ± 0.6 PgC yr −1 consistent with the independent top-down NEE from the global atmospheric carbon budget during 2000–2009. This estimate is so far the most comprehensive global bottom-up carbon budget accounting, which set up an important milestone for global carbon-cycle studies. By decomposing NEE into component fluxes, we found that global soil heterotrophic respiration amounts to a source of CO2 of 39 PgC yr −1 with an interquartile of 33–46 PgC yr −1 —a much smaller portion of net primary productivity than previously reported.